Nanoparticles-Polyaniline-Multiwalled Carbon Nanotubes for Determination of Organophosphate Pesticides - Wei, Min; Wang, Jingjing; Guo, Jingxuan; Lu, Qiyu (Asian Journal of Chemistry, 2014)
A sensitive, fast and stable amperometric acetylcholinesterase biosensor was developed based on gold nanoparticles-polyaniline-multiwalled carbon nanotubes (Au-PANI-MWCNTs) nanocomposite for quantitative determination of organophosphate pesticides. Because of the large surface areas and strong adsorptive ability of the Au-PANI-MWCNTs nanocomposite, the immobilized acetylcholinesterase developed high affinity for acetylthiocholine and exhibited excellent catalytic effect on the hydrolysis of acetylthiocholine. Based on the inhibition of organophosphorous pesticides on the activity of acetylcholinesterase, using parathion as a model compound, the conditions for detection of the pesticides were optimized. The inhibition of parathion was proportional to its concentration ranging from 0.2 to 2 nM and 8 to 100 nM with the correlation coefficients of 0.9982 and 0.9988, respectively. The detection limit was 0.062 nM. The developed biosensor exhibited good reproducibility and acceptable stability.